2021
DOI: 10.3390/ijerph18083910
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seroprevalence among Health Care Workers—A Voluntary Screening Study in a Regional Medical Center in Southern Germany

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is associated with a potentially severe clinical manifestation, coronavirus disease 2019 (COVID-19), and currently poses a worldwide challenge. Health care workers (HCWs) are at the forefront of any health care system and thus especially at risk for SARS-CoV-2 infection due to their potentially frequent and close contact with patients suffering from COVID-19. Serum samples from 198 HCWs with direct patient contact of a regional medical center and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(27 reference statements)
2
3
2
1
Order By: Relevance
“…Seroprevalence estimates of 1.2% in May/June 2020 and 4.6% in December 2020 found in our investigation were lower than the meta-analysis by Galanis et al reporting an overall pooled prevalence of 8.7% among all HCWs globally as well as 8.5% among HCWs in Europe. In contrast, other HCW studies in Germany have found similar estimates to our study, ranging from 1.6 to 5.1% across varying regions, HCW populations and time periods from March to July 2020 [ 14 20 ]. Korth et al found a similar increase in seroprevalence from 2.2% in March–May 2020 to 5.1% in October–December 2020 at a tertiary facility in Western Germany [ 17 ].…”
Section: Discussionsupporting
confidence: 83%
“…Seroprevalence estimates of 1.2% in May/June 2020 and 4.6% in December 2020 found in our investigation were lower than the meta-analysis by Galanis et al reporting an overall pooled prevalence of 8.7% among all HCWs globally as well as 8.5% among HCWs in Europe. In contrast, other HCW studies in Germany have found similar estimates to our study, ranging from 1.6 to 5.1% across varying regions, HCW populations and time periods from March to July 2020 [ 14 20 ]. Korth et al found a similar increase in seroprevalence from 2.2% in March–May 2020 to 5.1% in October–December 2020 at a tertiary facility in Western Germany [ 17 ].…”
Section: Discussionsupporting
confidence: 83%
“…Age and gender of the HCW, usage of PPE and adherence to IPC did not had significant association of seropositivity in our study, while those who had any symptom had lower risk of seroconversion. These are in contrast to study from similar settings in New Delhi observed seropositivity to be associated with male sex (31), while one from Germany observed use of PPE to be protective (35). A study from Spain reported high odds of seropositive among those having any COVID-19 symptom in the previous months, although found no association with profession, working in high risk unit, close contact with a COVID-19 case, comorbidities and sex, partially supporting our findings(16).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in line with other studies conducted in German hospitals, indicating a low prevalence of SARS-CoV-2 specific antibodies in HCWs [ 20 , 21 , 22 ]. For example, a seroprevalence of 3.5% was reported in HCWs with direct patient contact in a medical center in Southern Germany in April 2020 [ 23 ]. Similarly, the study of Korth et al conducted in HCWs at a German University Hospital reported a seroprevalence of 2.2% in March–May, which increased to 4.0% in June–July and to 5.1% in October–December 2020 [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%